Understanding the relationship between perceived stress, academic motivation, and physical activity in college students during the coronavirus pandemic - Rahe, Martina; Jansen, Petra (Frontiers in Education, 2022)
The Coronavirus Pandemic has influenced the life of many people. We analyzed the effects of physical activity and stress on students’ motivation during the Pandemic. Participants were 254 university students who reported their academic motivation, physical activity, general stress, strain of the Coronavirus Pandemic, and their Coronavirus stress. Women reported higher levels of Coronavirus stress, general stress, and motivation. The Coronavirus stress was predicted by the strain of the Coronavirus Pandemic but not by physical activity. Mastery goals were predicted by the general stress and gender and performance goals were predicted by the general stress. Physical activity could not explain any incremental variance of students’ motivation during the Pandemic. Higher levels of general stress were associated with a higher academic motivation. Negative emotions like stress could have enhanced students’ motivation during uncertain times of the Pandemic. Moreover, a moderate level of stress could be favorable for academic dedication and achievement.